PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT CAHAYAMULIA GLASSINDO LESTARI - Saputri, Intan Wahyuni; Purnamasari, Endah Dewi; Ulum, Muhammad Bahrul (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this research is to examine how factors like work load and workplace atmosphere affect productivity at PT Cahayamulia Glassindo Lestari. Saturated sampling was utilised in this quantitative study consisting of a total of 60 participants. Primary data was gathered using surveys and analysed with multiple linear regression techniques, the T-test, and the F-test. The F-test findings have been analysed, and since Fcount is more than 3.16 and the significance level is smaller than 0.05, we may accept H3. Therefore, it is determined that the workload and work environment at PT Cahayamulia Glassindo Lestari have a substantial impact on employee performance. Workload (X1) has a tcount of 2.937 2.002 and a significant value of 0.005 0.05, while Work Environment (X2) has a tcount of 5.195 2.002 and a significant value of 0.000 0.05, indicating that both variables significantly affect employee performance at PT Cahayamulia Glasindo Lestari. Workload and work environment, the two independent factors tested, explain 52.3% of the variance in employee performance.Keywords: workload, work environment, employee performance.